Bioinspired chemistry from enzymes to synthetic models (World Scientific Publishing Company Pte Limited, 2019)
"The observation of Nature is an inexhaustible source of inspiration to promote innovations in chemistry. The bioinspired approach is a revolution in our paradigms because it is not based on what we can take to nature, but on what we can learn from it. Enzymatic systems involved in solar energy conversion (photosystem), hydrogen production (hydrogenases), dioxygen activation (oxydases et oxygenases), CO₂ reduction (CO dehydrogenase) use abundant and cheap starting material such as O₂, H₂O and CO₂. Inspiration of these biological systems is a solution to make our chemical processes greener. These are some of the many challenges that bioinspired chemistry is able to take up. A number of the recent developments in bioinspired chemistry are discussed, including some descriptions on the biological systems that are the source of inspiration. This book is a guide to where bioinspired chemistry will be in the near future and provides a thoughtful perspective on how bioinspiration could change our world."--